DIGITAL MARKETING’S TRAINING AT CV JAMU BANDUNG - Noneng Nurjanah; Suci Fika Widyana; Dera Thorfiani; Ali Mohammad Rezza (Universitas INABA, 2022)
CV Jamu Bandung is a company in Bandung whose core business is producing traditional medicine, especially herbal medicine drinks, called jamu. The uniqueness of CV Jamu Bandung is that it uses a hereditary recipe with a delicious taste that is liked by millennials and youngsters who generally dislike herbal drinks. Cv Jamu Bandung only uses raw organic materials of high quality while its production process is conducted traditionally. It deploys digital marketing and social media marketing to sell its product. However, CV Jamu Bandung's digital marketing has not been implemented optimally. Therefore, there is a space for improvement, such as recreating its strategy and upgrading the skills of its employee. The activities include digital marketing training, theories, concepts, designing product sales content through digital marketing, and online customer service techniques. Implementation of the training results aims to increase CV Jamu Bandung's brand awareness, increase reach and understand how to establish online communication with customers and potential customers of CV Jamu Bandung.